Ultrathin PdAuBiTe Nanosheets as High‐Performance Oxygen Reduction Catalysts for a Direct Methanol Fuel Cell Device. Issue 42 (31st August 2021) - Zhao, Fengling; Zheng, Lirong; Yuan, Qiang; Yang, Xiaotong; Zhang, Qinghua; Xu, Han; Guo, Yuanlong; Yang, Song; Zhou, Zhiyou; Gu, Lin; Wang, Xun
Abstract: Ultrathin 2D metal nanostructures have sparked a lot of research interest because of their improved electrocatalytic properties for fuel cells. So far, no effective technique for preparing ultrathin 2D Pd‐based metal nanostructures with more than three compositions has been published. Herein, a new visible‐light‐induced template technique for producing PdAuBiTe alloyed 2D ultrathin nanosheets is developed. The mass activity of the PdAuBiTe nanosheets against the oxygen reduction reaction (ORR) is 2.48 A mgPd −1, which is 27.5/17.7 times that of industrial Pd/C/Pt/C, respectively. After 10 000 potential cyclings, there is no decrease in ORR activity. The PdAuBiTe nanosheets exhibit high methanol tolerance and in situ anti‐CO poisoning properties. The PdAuBiTe nanosheets, as cathode electrocatalysts in direct methanol fuel cells, can thus give significant improvement in terms of power density and durability. In O2 /air, the power density can be increased to 235.7/173.5 mW cm −2, higher than that reported in previous work, and which is 2.32/3.59 times higher than Pt/C. Abstract : Ultrathin quaternary PdAuBiTe alloyed 2D nanosheets are first achieved by a new visible‐light‐induced template strategy. As high‐performance oxygen reduction reaction (ORR) catalysts, the PdAuBiTe nanosheets can greatly increase power densities and durability in direct methanol fuel cell devices. The maximum power densities of PdAuBiTe nanosheets are up to 235.7/173.5 mW cm –2 in O2 /air, respectively.